2018
DOI: 10.5334/joc.12
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Dilation Reflects Task Relevance Prior to Search

Abstract: When observers search for a specific target, it is assumed that they activate a representation of the task relevant object in visual working memory (VWM). This representation – often referred to as the template – guides attention towards matching visual input. In two experiments we tested whether the pupil response can be used to differentiate stimuli that match the task-relevant template from irrelevant input. Observers memorized a target color to be searched for in a multi-color visual search display, presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…the location in the visual field to which these neurons respond); next, they flashed a stimulus either within, or outside of, the stimulated RF. Crucially, they observed a stronger PLR to stimuli flashed within the stimulated RF, compared to outside of the stimulated RF—a result that echoes behavioral studies (notably Binda & Murray, 2015; Olmos-Solis et al, 2018).…”
Section: The Pupil Light Responsementioning
confidence: 55%
See 4 more Smart Citations
“…the location in the visual field to which these neurons respond); next, they flashed a stimulus either within, or outside of, the stimulated RF. Crucially, they observed a stronger PLR to stimuli flashed within the stimulated RF, compared to outside of the stimulated RF—a result that echoes behavioral studies (notably Binda & Murray, 2015; Olmos-Solis et al, 2018).…”
Section: The Pupil Light Responsementioning
confidence: 55%
“…Crucially, the color of this probe either matched, or did not match, the memorized color. Olmos-Solis et al (2018) found that the pupil constricted more in response to memory-matching as compared to non-matching probes; in other words, when a stimulus matches the contents of visual working memory, it triggers a stronger PLR. This finding is again mediated by visual attention; more specifically, it is mediated by the fact that stimuli that match the contents of visual working memory tend to capture attention (e.g.…”
Section: The Pupil Light Responsementioning
confidence: 99%
See 3 more Smart Citations